Pengaruh Kreasi Kertas Kokoru Terhadap Perkembangan Kreativitas Anak Di Taman Kanak-Kanak Nurul Yakin Ringan-Ringan Kabupaten Padang Pariaman - Mia Amalia; Rismareni Pransiska; Yulsofriend Yulsofriend (Universitas Bengkulu, 2019)
This study aims to determine the effect of kokoru paper on the development of children's creativity. This study uses a quantitative approach in the form of experimental quasy. Based on data analysis, the average test results of the experimental class were 80 while the control class was 73.75. Based on the t-test calculation, t count is greater than t table, indicating that there are significant differences between the two classes. So it can be concluded that the creation of kokoru paper affects the development of children's creativity in the Nurul Yakin Ringan-ringan Kabupaten Padang Pariaman District in the 2018/2019 school year.